Down-regulation of ZNF252P-AS1 alleviates ovarian cancer progression by binding miR-324-3p to downregulate LY6K - Li Geng; Zhongqiu Wang; Yongju Tian (BMC, 2022)
Abstract Background Ovarian cancer is a common gynecological malignant disease in women. Our work aimed to study the specific functions of ZNF252P antisense RNA 1 (ZNF252P-AS1) in ovarian cancer. Methods ZNF252P-AS1, miR-324-3p, and lymphocyte antigen 6 family member K (LY6K) expression were analyzed by bioinformatics tools in ovarian cancer tissues and was quantified by qRT-PCR in ovarian cancer cells. The effect of ZNF252P-AS1 knockdown, miR-324-3p suppression, and LY6K over-expression on apoptosis, cell viability, invasion, migration, and epithelial to mesenchymal transition (EMT) was determined in vitro by using colony formation and EdU assays, flow cytometry, transwell assay, and Western blot. The interactions between ZNF252P-AS1 and miR-324-3p and between miR-324-3p and LY6K were validated by luciferase assays. The effects of restraining ZNF252P-AS1 in vivo were studied using BALB/c male nude mice. Results ZNF252P-AS1 and LY6K levels were up-regulated, while miR-324-3p was declined in ovarian cancer tissues and cells. ZNF252P-AS1 knockdown reduced ovarian cancer cell proliferation, invasion, migration, and EMT, whereas promoted its apoptosis. Besides, ZNF252P-AS1 interacted with miR-324-3p and reversely regulated its level, and miR-324-3p was directly bound to LY6K and negatively regulated its expression. Moreover, ZNF252P-AS1 knockdown reversed the effect of miR-324-3p on cancer cell apoptosis, growth, migration, invasion, and EMT. Similar results were discovered in the rescue experiments between miR-324-3p and LY6K. Additionally, mouse models in vivo experiments further validated that ZNF252P-AS1 knockdown distinctly inhibited tumor growth. Conclusion ZNF252P-AS1 mediated miR-324-3p/LY6K signaling to facilitate progression of ovarian cancer.